MICROPROPAGATION OF HYPERICUM TRIQUETRIFOLIUM - AkÃ§am, E. O.; Orhan, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Hypericum perforatum is commonly used as a medicinal plant for its anti-depressant properties. Several constituents of the plant, such as hypericin and hyperforin, seem to be important for these properties. Another Hypericum cultivar, Hypericum triquetrifolium natives to eastern Europe and the Mediterranean area is also known to carry same anti-depressant compounds. Harvesting the medicinal plants from the wild is causing loss of genetic diversity. On the other hand one of the main characteristics desired for pharmaceutical application is stable content of active compound as not in the raw material obtained from wild plants. Also some medicinal plants have very small seeds like Hypericum triquetrifolium can not be cultured with traditional methods. For solving this problems in vitro culture methods are suggested by many researchers. We aim to establish a micropropagation protocol for Hypericum triquetrifolium. As starting material native seed were used. After an affective germination period on water-agar, seedlings were transferred 10 different shoot multiplication medium including Murashige&Skoog (MS) bazal media supplemented with different concentrations of [N-phenyl-Nb-(1,2,3 thidiazolyl) urea], benzyladenine and indoleacetic acid. The best shoot development in explants was obtained on MS medium supplemented with 1.25 mg/L thidiazuron and supplemented with 0.5 mg/L indoleacetic acid. Root development was obtained on MS medium supplemented with IAA or hormone free medium. Micropropagated plants were transferred to greenhouse successfully. All cultures were incubated at 27 ± 40C under a light intensity of 4000 lux, with 16 hour photoperiod. Key words: Hypericum triquetrifolium, micropropagation, medicinal plant.